Epidemiology, risk of malignancy and patient survival in primary sclerosing cholangitis: a population-based study in Finland. (2nd January 2020) - Barner-Rasmussen, Nina; Pukkala, Eero; Jussila, Airi; Färkkilä, Martti
Abstract: Background: There are only a few and mostly small population-based epidemiological studies of primary sclerosing cholangitis (PSC). Objective: We aimed to estimate prevalence and incidence rates of PSC, and survival and malignancy risk for PSC patients in a large population-based study. Methods: We retrieved 632 PSC patients from 1990 to 2015 in the Hospital District of Helsinki and Uusimaa (HUS), comprising 29% of the Finnish population. Mortality information of the PSC patients was obtained from the national Population Registry, malignancy information from the Finnish Cancer Registry and the causes of death from the Statistics Finland. Standardized incidence ratio and standardized mortality ratio (SMR) were calculated for predefined malignancy types. Results: The crude incidence of PSC in the HUS area was 1.58/100, 000 person-years, and the point prevalence in 2015 was 31.7/100, 000 inhabitants. The mean time from diagnosis to death was 21.9 years. The risk for any malignancy was three-fold and the risk for colorectal carcinoma was five-fold when comparing with the general population. During the first year after diagnosis of PSC, the risk for cholangiocarcinoma is 900-fold compared to the general population and after that 150-fold. SMR for all malignant neoplasms was 5.9 (95% CI 4.2–8.1). Conclusion: We found that the incidence of PSC in the HUS area in Finland is similar or higher than previously reported from other countries. The prevalence is markedly higher than reported elsewhere, probably due to the active search of the disease, suggesting that the disease is underdiagnosed.